2009
DOI: 10.1215/00031283-2009-030
|View full text |Cite
|
Sign up to set email alerts
|

Operationalizing Style: Quantifying the Use of Style Shift in the Speech of African American Adolescents

Abstract: The vast majority of research to date on African American Vernacular English style shift has taken the form of qualitative analyses of individual case studies; however, despite its great success, in focusing on individual rather than group style and style shifting, such work by itself is unable to answer key questions about style and style shift at the level of social groups, communities of practice, and broader based communities. Recent quantitative analyses, such as Craig and Washington's (2006) Dialect Dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…The emergence of adult-like patterns of style shifting appear to be in place at least at pre-adolescence (e.g., Hoyle and Adger 1998;Cheshire 1978Cheshire , 1982Purcell 1984;Renn and Terry 2009) with evidence of meta-awareness of informal and formal variants also attested (e.g., Reid 1978;Romaine 1978Romaine , 1984Chevrot et al 2000). Studies which include a range of ages may provide further insights.…”
Section: Style Shiftingmentioning
confidence: 98%
See 1 more Smart Citation
“…The emergence of adult-like patterns of style shifting appear to be in place at least at pre-adolescence (e.g., Hoyle and Adger 1998;Cheshire 1978Cheshire , 1982Purcell 1984;Renn and Terry 2009) with evidence of meta-awareness of informal and formal variants also attested (e.g., Reid 1978;Romaine 1978Romaine , 1984Chevrot et al 2000). Studies which include a range of ages may provide further insights.…”
Section: Style Shiftingmentioning
confidence: 98%
“…How much earlier, however, is still subject to some debate. Some suggest that systematic patterns are acquired in the preadolescent years e.g., 10-12 (e.g., Reid 1978;Renn and Terry 2009;Romaine 1984;Chevrot et al 2000), others in the first school years i.e., 6-8years old (e.g. , Labov 1989;Patterson 1992).…”
Section: Introductionmentioning
confidence: 99%
“…A followup to the Montreal French panel study (Sankoff, Wagner, & Jensen, forthcoming) found that speaker style had no significant effect on the increase in inflected future use over panelists' life spans. Renn (2009Renn ( , 2011 and Renn and Terry (2009) measured style-shifting for 43 of the panelists in the Van Hofwegen and Wolfram data, finding that speakers' range of style generally increased as they aged. Ultimately, however, neither of the large studies can explain the individual differences without more detailed ethnographic information, whereas the smaller studies are unable to untangle the effects of social and/or stylistic factors.…”
mentioning
confidence: 99%
“…Wolfram and colleagues (Renn & Wolfram, 2009; Van Hofwegen & Wolfram, 2009) have hypothesized that AAE feature production rates are age-graded, with peak periods prior to first grade, a dip between first and fourth grades, and increasing usage beyond fourth grade. Although no direct comparisons between children and adults were possible in this study, the present findings are suggestive that early adulthood may be another period of relatively high usage.…”
Section: Discussionmentioning
confidence: 99%
“…Oetting and Pruitt (2005) demonstrated that focusing on a smaller core set of AAE features rather than a larger range of potential features when calculating DDM was informative and highly efficient. Overall DDMs are robust, and minor variations in the calculation method yield relatively inconsequential differences (Renn & Terry, 2009). …”
Section: Sources Of Systematic Variationmentioning
confidence: 99%